Global Warming and Liquified Natural Gas (LNG) - Environmental Defense Center; California Coastal Protection Network (Environmental Defense Center)
A fact sheet provided by the Environmental Defense Center and California Coastal Protection Network that talks about global warming and how LNG could potentially add on to the growing problem.